When the burger becomes halal: a critical discourse analysis of privilege and marketplace inclusion. Issue 6 (2nd November 2017) - Johnson, Guillaume D.; Thomas, Kevin D.; Grier, Sonya A.
ABSTRACT: Although a rich body of research provides insights to understanding stigma within the marketplace, much less is known regarding its direct corollary, privilege. We posit that this void is problematic as it may inadvertently support and legitimate existing socio-political arrangements which inhibit consumer wellbeing and marketplace equality. The present study addresses this gap by offering a theoretical understanding of privilege within the marketplace. Using a Foucauldian approach to privilege and power, we draw on the discursive perspective on legitimation to critically investigate the contentious debate over the inclusion of halal meat at a popular burger chain in France. In light of French political secularism (laïcité), we demonstrate how power discursively operates through narratives on rights and moral responsibility to constitute, defend and challenge a certain state of privilege within the marketplace. Our resulting theoretical discussion extends existing studies on marketplace equality and the growing body of literature related to the "marketization of religion".